Amantadine and memantine: a comprehensive review for acquired brain injury. (23rd February 2020) - Ma, Heather M.; Zafonte, Ross D.
ABSTRACT: This comprehensive review discusses clinical studies of patients following brain injuries (traumatic, acquired, or stroke), who have been treated with amantadine or memantine. Both amantadine and memantine are commonly used in the acute rehabilitation setting following brain injuries, despite their lack of FDA-approval for neuro-recovery. Given the broad utilization of such agents, there is a need to review the evidence supporting this common off-label prescribing. The purpose of this review is to describe the mechanisms of action for memantine and amantadine, as well as to complete a comprehensive review of the clinical uses of these agents. We included 119 original, clinical research articles from NCBI Medline, published before 2019. We focused on the domains of neuroplasticity, functional recovery, motor recovery, arousal, fatigue, insomnia, behavior, agitation, and cognition. Most of the existing research supporting the use of amantadine and memantine in recovery from brain injuries was done in very small populations, limiting the significance of conclusions. While most studies are positive; small effect sizes are usually reported, or populations are subject to bias. Furthermore, evidence is so limited that this review includes research regarding both acute and chronic acquired brain injury populations. Fortunately, reported short-term side effects generally are modest, and stop soon after amantadine/memantine is discontinued. However, responses are inconsistent, and the phenotype of responders remains elusive.